The impact of corporate governance mechanisms on the performance of commercial banks: The case of private banks in Ethiopia - Wondimeneh Asrat Yihun; Abiy Getahun Kolech; Million Gizaw Tole (Financial Studies, 2019)
This study seeks to see the level of impacts that different corporate governance mechanisms has on financial performance of banks in Ethiopia. Explanatory research design was used in establishing the casual effect relationship between corporate governance variables and banks financial performance measures. Secondary data were collected from the banks' annual reports and the NBE. The study utilized panel data analysis methodology in drawing conclusion about the study covering ten-year period from 2006-2015. The fixed effect model was applied to allow heterogeneity among 7 banks. The regression results show that presence of female directors and industry specific experience of directors has positive and significant effects on financial performance of private banks while number of board committees has significant negative effects on bank performance. The study results implied that stakeholders should give prior considerations to the presence of female directors and industry specific experience of directors when they set governance policy for industry in general and for the bank in particular.
Keywords: G34; 330; Agency theory; banks; financial performance